Von Willebrand Disease and Angiodysplasia: a wider view of pathogenesis in pursuit of therapy - Christina Crossette-Thambiah; Anna M. Randi; Michael Laffan (Haematologica)
Bleeding in the GI tract continues to pose a therapeutic challenge for clinicians in patients with Von Willebrand Disease (VWD). It is associated with significant morbidity and mortality and represents the major unmet need in VWD. Defective angiogenesis in the gut is primarily responsible, resulting in angiodysplastic malformations making bleeding notoriously refractory to standard replacement therapy. A substantial body of evidence now shows that Von Willebrand Factor (VWF) has a role in the regulation of angiogenesis but the mechanisms responsible for the formation of vascular malformations remain incompletely understood. Data from the wider field of vascular malformations may lend insight and point to novel therapeutic approaches. Here we review evidence linking VWF to angiodysplasia, the associated molecular mechanisms and the implications for therapy.